Functional states in tumor-initiating cell differentiation in human colorectal cancer - Zowada, Martina; Tirier, Stephan Marius; Dieter, Sebastian M.; Krieger, Teresa G.; Oberlack, Ava; Chua, Robert Lorenz; Huerta, Mario; Ten, Foo Wei; Laaber, Karin; Park, Jeongbin; Jechow, Katharina; Müller, Torsten; et al. (Cancers, 2021)
Intra-tumor heterogeneity of tumor-initiating cell (TIC) activity drives colorectal cancer (CRC) progression and therapy resistance. Here, we used single-cell RNA-sequencing of patient-derived CRC models to decipher distinct cell subpopulations based on their transcriptional profiles. Cell type-specific expression modules of stem-like, transit amplifying-like, and differentiated CRC cells resemble differentiation states of normal intestinal epithelial cells. Strikingly, identified subpopulations differ in proliferative activity and metabolic state. In summary, we here show at single-cell resolution that transcriptional heterogeneity identifies functional states during TIC differentiation. Furthermore, identified expression signatures are linked to patient prognosis. Targeting transcriptional states associated to cancer cell differentiation might unravel novel vulnerabilities in human CRC.
Gesehen am 30.07.2021